2018
DOI: 10.3390/rs10111826
|View full text |Cite
|
Sign up to set email alerts
|

The VIIRS Sea-Ice Albedo Product Generation and Preliminary Validation

Abstract: Ice albedo feedback amplifies climate change signals and thus affects the global climate. Global long-term records on sea-ice albedo are important to characterize the regional or global energy budget. As the successor of MODIS (Moderate Resolution Imaging Spectroradiometer), VIIRS (Visible Infrared Imaging Radiometer Suite) started its observation from October 2011 on S-NPP (Suomi National Polar-orbiting Partnership). It has improved upon the capabilities of the operational Advanced Very High Resolution Radiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…-When compared to the LUT-based method for albedo retrieval (e.g. Qu et al (2016); Peng et al (2018)), this method is advantageous in terms of obtaining the underlying logic of the training data, availed by the RTM/SciML model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-When compared to the LUT-based method for albedo retrieval (e.g. Qu et al (2016); Peng et al (2018)), this method is advantageous in terms of obtaining the underlying logic of the training data, availed by the RTM/SciML model.…”
Section: Discussionmentioning
confidence: 99%
“…Although the OLCI-albedo product is the successor of MERIS (Istomina, 2020), which was also generated based on the melt-pond detector (MPD) algorithm (Zege et al, 2015), a comparison of the OLCI-albedo with aircraft observations (see Section 4.3) reveals an overestimation of the OLCI-albedo over the snow-covered sea-ice surface. The two direct-estimation products (hereafter referred as Qu's and Peng's, Qu et al (2016); Peng et al (2018))…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PROMICE data provide almost the same BBA (0.8) for the EGP and KAN-U sites. Peng et al (2018) have found that PROMICE data is biased low as compared to VIIRS satellite albedo retrievals. We have arrived to the same conclusion as far as OLCI retrievals are of concern for retrievals over EGP site.…”
Section: Broadband Albedomentioning
confidence: 96%
“…Stroeve’s work set the stage for numerous subsequent evaluations of Greenland snow and ice albedo changes (e.g. Tedesco et al, 2011; Box et al, 2012; Peng et al, 2018) with the advantages of advanced sensors, better image geolocation, higher spatial and spectral resolution, and the ease of much greater and less costly data storage.…”
Section: Pioneering the Use Of Satellite Remote Sensing In Cryosphere Studiesmentioning
confidence: 99%